Unit-Cost Calculation of Delivered Services Based on Activity Based Costing (ABC) Method Compared with Approved Tariffs in Physiotherapy Department of Sina Hospital Affiliated to Tehran University of Medical Sciences in 2013-2014 - Raziye Beyranvand; Farbod Ebadi Fard Azar; Sara Emamgholipour; Mohammad Arab (Tehran University of Medical Sciences, 2016)
Background: Todays, hospitals are facing with shortage of resources and increasing costs challenges, So, cost information and cost calculation of hospital delivered services can be effective in efficient resources allocation and tariff rates reforming and budget. This study aimed at calculating the cost of services and  physiotherapy departmentchr('39')s income of Sina hospital and comparing with approved tariffs in 2013-2014. Materials and Methods: This study was a cross sectional and retrospective one. The cost price of 13 physiotherapy services calculated using Activity Based Costing method for physiotherapy unit of Sina hospital of Tehran in 2013-2014. Data collection tool included some forms related to services costs of physiotherapy and related activity centers. Also, in order to estimate cost proportion of other wards in physiotherapy unit, the proportional allocation bases was determined, then direct allocation method was utilized. Results: The most costs of 13 provided services were less than tariffs in 2013. Generally, the costs pertain of physiotherapy services computed 794286777 Rials which workforce costs (48.4 percent) was the most proportion and then energy buildings depreciation and equipment costs. This issue is due to equipment dependency in physiotherapy unit services. Conclusions: study results revealed there was difference between real cost of services and approved tariffs, therefore, in order to more accurate pricing, exact calculation methods such as Activity Based Costing recommended. Considering high personnel and capital costs pay special attention to these resources, appropriate use, identifying and omitting wasted costs can be effective in increasing efficiency and saving costs.